Association of obesity- and insulin resistance-related indices with subclinical carotid atherosclerosis in type 1 diabetes: a cross-sectional study - Dongli Yang; Jie Zhou; Malgorzata A. Garstka; Qian Xu; Qiaoyue Li; Li Wang; Lijun Ren; Qiuhe Ji; Tao Liu (Cardiovascular Diabetology)
Abstract Background Obesity and insulin resistance are well-established risk factors for atherosclerosis and cardiovascular disease (CVD). Although some obesity- and insulin resistance-related indices (OIRIs) have been linked to CVD, their associations with subclinical carotid atherosclerosis (SCA) in individuals with type 1 diabetes (T1D) remain unclear. This study aims to systematically explore and compare the associations of various common OIRIs with SCA in T1D population. Methods A total of 418 adult inpatients with classic T1D admitted from October 2008 to June 2021 to the First Affiliated Hospital of Air Force Medical University in Xi’an, China were included in this study. Demographic, anthropometric, and laboratory data were collected. Studied OIRIs comprised body mass index, waist-to-height ratio, waist-to-hip ratio (WHR), a body shape index, abdominal volume index, body adiposity index, body roundness index, conicity index, triglyceride-glucose index, visceral adiposity index, Chinese visceral adiposity index (CVAI), lipid accumulation product, estimated glucose disposal rate (eGDR), triglyceride-to-HDL ratio, and cardiometabolic index. Binary logistic regression, restricted cubic spline (RCS), and receiver operating characteristic curves were used to examine the associations of these indices with SCA. Results In multivariable logistic regression analyses, after adjusting for potential confounders, per 1.0-standard deviation (SD) increase in CVAI (OR, 95% CI: 1.68, 1.16–2.47), eGDRWHR (eGDR calculated with WHR; OR, 95% CI: 0.44, 0.22–0.82), and eGDRWC (eGDR calculated with waist circumference; OR, 95% CI: 0.49, 0.24–0.93) were significantly associated with SCA. CVAI exhibited the highest area under the curve (AUC) in diagnosing SCA, with a value of 0.73 (95% CI: 0.69–0.77). RCS analyses indicated a linear and positive association between CVAI and SCA in the overall population and the females. Subgroup analyses and sensitivity analyses further supported the association between CVAI and SCA. Additionally, adding CVAI to the Steno Type 1 Risk Engine (ST1RE) improved the reclassification, but did not enhance the overall discriminative ability of ST1RE to identify SCA. Conclusion Among various OIRIs, CVAI shows the strongest association with SCA in adults with T1D. These findings suggest that CVAI may merit further longitudinal investigation as a potential marker for SCA assessment in this population. Graphical abstract